PTU-082 Serum CEACAM1 in the preclinical diagnosis of pancreatic adenocarcinoma. (23rd September 2015) - Sandanayake, N S; Andreola, F; Camuzeaux, S; Sinclair, J; Chapman, M H; Webster, G J; Gentry-Maharaj, A; Menon, U; Jacobs, I; Smith, R C; Pereira, S P; Timms, J F
Abstract : Introduction: There are currently no early detection serum biomarkers for diagnosing pancreatic ductal adenocarcinoma (PDAC). Carcinoembryonic Antigen-related Cell Adhesion Molecule 1 (CEACAM1) is a member of the human carcinoembryonic antigen family. It has recently been shown to be overexpressed in pancreatic adenocarcinoma tissue and precursor PanIN-3 lesions, while serum levels demonstrate superior sensitivity and specificity to CA19.9 in patients with pancreatic cancer.1 The UK Collaborative Trial of Ovarian Cancer Screening (UKCTOCS) is the largest ever randomised control trial and has enabled the collection of sera from women pre-dating diagnosis of a variety of diseases, including 308 women who have developed PDAC. Serum CEACAM1 levels were evaluated in this population and healthy controls. Methods: Blood was collected in clot tubes from healthy post-menopausal women aged 50–74 years at designated regional centres following informed consent and sent to the UKCTOCS processing facility within 48 h. Samples were centrifuged, aliquoted into 0.5 ml cryostraws, frozen at −80°C and then stored in liquid nitrogen. Women in the cohort with a diagnosis of pancreatic cancer were identified by cross-referencing with the Office of National Statistics Codes and Death Codes. Once a case was identified, a healthy age-matched control was obtained and the paired serum samples analysed. Human CEACAM1/CD66a DuoSet ELISA kit (R&D Systems) was used to assay serum. The coefficient of variation for the assay was 11%. Samples were run in duplicate after at most two freeze-thaw cycles. Cases and healthy controls were separated into groups depending on time to diagnosis. Results: In the 0–6 months pre-diagnosis time group, the mean CEACAM1 level was 62.6 ng/ml for cases (n=17) vs 40.2 ng/ml for matched controls (n=18) (p=0.035). In all controls (n=111) mean CEACAM1 was 46.9 ng/ml, improving the significance against cases (p=0.006). There was no significant difference in CEACAM1 levels in the other time groups. CA19.9 assays are underway for comparison. Conclusion: Serum CEACAM1 was significantly elevated in women who were within 6 months of a diagnosis of PDAC. This serum biomarker may have potential use in pancreatic cancer screening.